Case report: full recovery from dialysis-requiring renal failure after surgical repair of a completely occluded renal artery in a patient with a single kidney - Marta Kantauskaite; Klaus Grabitz; Lars Christian Rump; Sebastian Alexander Potthoff (BMC Nephrology)
Abstract Introduction Renal infarction is an extremely rare condition occurring in the context of structural or functional cardiac abnormalities, renal artery injury or coagulative syndromes. Although the clinical presentation of renal infarction is often nonspecific, the presence of symptoms such as back pain, high blood pressure, nausea and fever should raise suspicion, particularly in the emergency setting. Timely diagnosis is crucial for preserving renal function, whether through minimally invasive procedures or bypass surgery. Case presentation We present a case of a young male who developed acute occlusion of an aortic-renal bypass supplying a solitary left kidney. The patient exhibited resistant arterial hypertension and acute oligo-anuric kidney injury requiring dialysis. Despite the total occlusion of the aorto-renal bypass on imaging, doppler ultrasound demonstrated moderate renal tissue perfusion, likely maintained via collateral vasculature. The existence of a previous prolonged ischemic condition may have led to the formation of collateral-dependent circulation. While insufficient for pressure-dependent diuresis, the collateral flow preserved renal tissue oxygenation. Conclusions Collateral perfusion should be evaluated in cases of renal infarction, particularly when the main renal artery is occluded. Adequate collateral circulation might preserve renal tissue viability beyond the typical ischemic window.